(untitled) (Baghdad Science Journal, 2007)
The present research aims at recognizing the difficulties and problems which hamper teachers and educators alike when using the internet for educational purposes.It discusses the benefits of the internet as a source of information or publication and as a communicative tool.Arandom sample of (30) teachers working at schools in Baghdad / Second Risafa,was selected.Three of the sample members use the internet for student project plans via internet centers, whereas 16 of them use it for chatting, emailing and research purposes.The rest of the sample have limited knowledge of the internet. The researcher used the interviewing method to gather data from the sample members.The method involved eleven questions which required their replies.The repeated distribution and the percentage were employed to analyze the collected data.Among the conclusions arrived at is that the difficulties confronted by the teachers are their computer and internet illiteracy, particularly in teaching sciences, lack of internet and computer training courses,unavailability of computers, shortage of computer and internet guides and manuals which,even when available,do not match the ongoing progress,lack of technical support,continuing power failure, high cost of computers and internet access systems, anxiety and fear of misusing the internet, which led to negative orientation in internet use,fear of accessing non-educational sites,fear of losing focus when browsing the web, in addition to the teachers’ lack of knowledge of other languages such as the English. The study makes the following recommendations.It recommends that the Ministry of Education should provide computers which are connected to the internet.Computer and internet training courses must also be held to provide teachers with the skills they need to use the internet in teaching science.There should also be curricula prepared which include the use computers and the internet in most subjects, particularly science.Material and technical support should also be provided for schools.